Implementasi Manajemen Strategis dalam Meningkatkan Mutu Pendidikan - Isma Hasyim Fanani; Farikhul Anwar (Pascasarjana Universitas Qomaruddin, 2023)
In facing the phenomenon of increasingly rapid development and increasing competition between schools, schools need to implement various good strategies. Strategic management is the right choice to overcome this challenge because it focuses on future planning and is based on analysis of the internal and external environment. By following the process of strategic management stages, schools can carefully consider appropriate decisions, follow-up actions and strategic choices to respond to the dynamics of development and changes in the educational context. The research method used is qualitative, with data collection techniques in the form of observation, interviews and documentation. The research results concluded that the strategic management of MA Darul Ulum Ngabar was effective in improving the quality of education. Strategic planning includes steps such as developing a vision, mission and goals, identifying internal and external factors through SWOT analysis, short-term, medium-term and long-term planning, and determining a good strategy. This process requires the cooperation of all stakeholders, including the seminary principal, assistant director of communications, assistant director of curriculum, assistant dean of students, teachers, and the seminary committee. The implementation of strategic management includes madrasa policies, motivation of educators and education staff, mobilization of human resources, and development of madrasa culture. The results include improved staff performance, effective learning processes, improved student performance, higher competency standards, and higher attractiveness in the eyes of society.